Protective effect of casuarinin against glutamate-induced apoptosis in HT22 cells through inhibition of oxidative stress-mediated MAPK phosphorylation. Issue 23 (1st December 2017) - Song, Ji Hoon; Kang, Ki Sung; Choi, You-Kyung
Graphical abstract: Abstract: Glutamate is the major excitatory neurotransmitter in the central nervous system and is involved in oxidative stress during neurodegeneration. In the present study, casuarinin prevented glutamate-induced HT22 murine hippocampal neuronal cell death by inhibiting intracellular reactive oxygen species (ROS) production. Moreover, casuarinin reduced chromatin condensation and annexin-V-positive cell production induced by glutamate. We also confirmed the underlying protective mechanism of casuarinin against glutamate-induced neurotoxicity. Glutamate markedly increased the phosphorylation of extracellular signal regulated kinase (ERK)-1/2 and p38, which are crucial in oxidative stress-mediated neuronal cell death. Conversely, treatment with casuarinin diminished the phosphorylation of ERK1/2 and P38. In conclusion, the results of this study suggest that casuarinin, obtained from natural products, acts as potent neuroprotective agent by suppressing glutamate-mediated apoptosis through the inhibition of ROS production and activation of the mitogen activated protein kinase (MAPK) pathway. Thus, casuarinin can be a potential therapeutic agent in the treatment of neurodegenerative diseases.